Development of conceptual bases of the employee life cycle within an organization - Gladka, Olena; Fedorova, Victoria; Dohadailo, Yana (Business: Theory and Practice, 2022)
The purpose of the study is to review and integrate various definitions of the employee life cycle (ELC) and to develop new conceptual bases of ELC by applying logical analysis and systemic approach. In this article, we suggest the employee life cycle has a “client-based” approach. Therefore the development of the ELC is similar to the development of the client life cycle and each stage of this process requires adoption and use of external and internal personnel marketing tools. At the same time, it implies simultaneous various activities of employees and employers alike. A customer-centric process on the labor markets (external and internal) is initiated by the personnel marketing product. It is defined by three levels aiming to attract and retain employees. The model of the ELC proposed hereafter shows the bilateral mechanism of the employee-employer interaction. Through the activities of external (employee attraction) or internal (employee retention) personnel marketing the organization can build its “perceived” or “received” Employer Value Proposition (EVP). The refined definition of the ELC is based on the theoretical foundations of personnel marketing and takes into account the employee and the employer’s perspectives; our definition identifies the ELC time frame and defines indicators of the ELC measurement for further empirical studies. Suggested ELC stages were developed in a way to reflect characteristics and actions for the employer and the employee simultaneously. To maintain or renew the employee engagement level a set of measures were suggested for implementation at each stage of the ELC.